Analisis Bukti Serangan Address Resolution Protocol Spoofing menggunakan Metode National Institute of Standard Technology - Imam Riadi; Abdul Fadlil; Muhammad Nasir Hafizh (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
This research intends to find information about evidence of Address Resolution Protocol (ARP) Spoofing attacks that is the MAC address of the attacker and victim also the time of the attack. This research uses Wireshark tools to inspect network traffic, especially on the ARP protocol. It uses the National Institute of Technology Technology (NIST) method as a framework in the simulation process to produce evidence reports. ARP Spoofing attacks can lead to other attacks, such as Denial of Service and Man in the Middle Attack, this attack allows users not to be able to access the network and data theft. During the simulation stage, 2 ARP Spoofing attacks are carried out on 1 laptop and 1 router connected to the network. The results of the attack simulation found 2 attacks and obtained information about the MAC address of the attacker and victim and also the time of the attack. Based on the results of tests carried, successfully found all ARP Spoofing attacks that occur on the network with a success rate of 100%